INOVASI MOBILE DIGITAL VIDEO RECORDER (MDVR) MENGURANGI RISIKO KECELAKAAN TAMBANG NIKEL PT PPA - Ashthofi Zainati; Rayhan Fadhillah; Fikri Fahmi Amrulloh3; Sukardi Yusuf (Jurnal Kesehatan Lentera 'Aisyiyah, 2025)
The mining industry faces a high risk of work-related accidents, often caused by fatigue and lack of supervision. PT Putra Perkasa Abadi (PPA), which experienced a fatigue-related incident in 2023, implemented the "Eagle Eyes" program at its MLP Site starting in 2024. This program utilizes Mobile Digital Video Recorder (MDVR) technology integrated with a Driver Monitoring System (DMS) and Advanced Driver Assistance Systems (ADAS). This study aims to analyze the effectiveness of the Eagle Eyes program in reducing accident risk. The method used is descriptive quantitative, monitoring 285 dump truck operators in real-time. The results from the April-July 2025 period show a significant decrease in key risk factors. Eyes Closed (fatigue indicator) findings dropped from 29,353 to 12,613 cases, Yawning dropped from 7,608 to 1,143 cases, and Phone Call Alarm (distraction) dropped from 431 to 87 findings. This study concludes that the Eagle Eyes program successfully reduced fatigue-related incidents and distractions, strengthening the behavior-based safety culture at PT PPA Site MLP.